2015
DOI: 10.1002/jsfa.7276
|View full text |Cite
|
Sign up to set email alerts
|

Folate distribution in barley (Hordeum vulgare L.), common wheat (Triticum aestivum L.) and durum wheat (Triticum turgidum durum Desf.) pearled fractions

Abstract: Results proved that folates are mainly present in the germ and in the outer layers of the kernel. This is the first study reporting the folate distribution in kernels of both common and durum wheat and in a hulless barley cultivar. Results suggest that the pearling process could be useful for the selection of intermediate fractions that could be used in order to develop folate-enhanced ingredients and products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…As a result, malignant cells are unable to synthesize DNA and RNA, leading to cell apoptosis (35). This confirms the findings of previous studies emphasizing the crucial role of folates in root development (36,37). Cantharidin is a natural substance, secreted by blister beetles, particularly Lytta vesicatoria , which inhibits protein phosphatase 2A.…”
Section: Discussionsupporting
confidence: 92%
“…As a result, malignant cells are unable to synthesize DNA and RNA, leading to cell apoptosis (35). This confirms the findings of previous studies emphasizing the crucial role of folates in root development (36,37). Cantharidin is a natural substance, secreted by blister beetles, particularly Lytta vesicatoria , which inhibits protein phosphatase 2A.…”
Section: Discussionsupporting
confidence: 92%
“…Green malt has the highest functional ingredients including antioxidant activity (79.80%), total phenolic (122.43 mg/100 g), (+)-catechin (69.06 mg/100 g), quercetin (30.78 mg/100 g), 1,2-dihydroxybenzene (37.21 mg/100 g), isorhamnetin (22.44 mg/100 g), and carotenoid (0.171 mg/100 g) [22]. The germ and the outer layers of hulless barley grains have the highest folate concentration (103.3 mg/100 g) [23]. The average concentrations of K, Ca, and Fe in barley grass powder were 6.7, 12.0, and 4.6 times that of barley grains, especially the qK1/qMg1/qCa1 region with large additive effects in Bmag0211~GBMS0014 on chromosome 1H [24].…”
Section: Functional Ingredients In Barleymentioning
confidence: 99%
“…The GABA has a very important role in mediating NaCl stress phenolic compounds accumulation in germinated hulless barley [38]. Linoleic acid content increased from 51.74% to 56.56% and oil from 1.73 to 2.13%, while oleic content decreased from 19.94% to 15.62% and palmitic acid from 18.53% to 17.33% during barley malting process [23].…”
Section: Tocolsmentioning
confidence: 99%
“…8 (Pioneer 3245, 2011 growing season). The total folate content was determined through a microbiological assay according to the AOAC Method 2004.05 (DeVries et al, 2005, with a few modifications, as reported by Giordano et al (2016a). The amount of folate in each sample was determined through a comparison with calibration curves of folic acid (Sigma-Aldrich, Saint Luis, Missouri).…”
Section: Analysis Of the Total Folate Contentmentioning
confidence: 99%